Assessing the Economic Impact of Jhelum Basin’s River WaterResources in Kashmir - Shahid Gul; Swadesh Prakash; Qureshi, Neha W.; Yadav, Vinod Kumar; Arpita Sharma; Mir, Shakir Ahmad (Journal of Indian Fisheries Association, 2023)
This study endeavors to ascertain the quantifiable value attributed to the utilization of river water for potablepurposes within the Jhelum basin of Kashmir. A meticulous investigation was conducted, centering on theKakapora Water Treatment Plant located in the Pulwama district, for the purpose of executing acomprehensive cost-benefit analysis. Drawing insights from the Jammu and Kashmir census report of 2011,alongside data provided by the Jammu & Kashmir Infrastructure Development Finance Corporation Limited(JKIDFC) in 2019, it is established that a substantial 0.0563 million households rely on river water forconsumption. The aggregate volume of water consumed by the entirety of this populace translates to astaggering 1.552 million gallons per day. Notably, the government's investment in this endeavor emerges as afinancially advantageous venture, as evidenced by a favorable benefit-cost ratio (BCR) of 1.014. In-depthscrutiny of the costs involved revealed that annual variable expenses account for Rs.1.934 million (31.3%),while fixed costs amount to Rs. 4.246 million (68.7%). Moreover, the precise evaluation of the cost andassociated value (price) per liter of filtered water culminates in figures of Rs.0.0499 and Rs.0.0504respectively. Further magnifying the significance of these findings, the total water consumption by anestimated 0.301 million individuals over a year equates to a voluminous 566.3 million gallons, carrying anestimated valuation of Rs.108 million. By quantifying the pivotal role played by river water in the Jhelum basin,this study contributes significantly to the existing body of scholarly literature. It marks a pioneering effortwithin the region, holding the potential to inform and shape judicious policies aimed at optimizing themanagement of this precious resource.